The Campaign of Papua Peace Network for Papua Peace Land - Cahyo Pamungkas (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This article aims to narrate a series of peaceful campaigns conducted by Papua Peace Network (PPN) for Papua Peace Land. This informal network consists of several groups of civil societies, such as religious organizations, ethnic groups, NGOs, and academicians. The PPN has some objectives that are to connect conflicted groups in Papua land, and to help both Papuan people and Indonesian government preparing an inclusive dialogue. This article results from research between 2013 and 2017. The data collection used observation of peaceful campaign of PPN, interviews, and archival research. This research shows that although a series of peaceful campaigns have been conducted by PPN both at the national and local levels between 2013 and 2016, but political violence still increases in Papua land. On another side, the national government only focuses on social and economic development issues, in particular, infrastructure projects, instead of political issues. Government officials involved in peaceful campaigns conducted by PPN had no power enough to implement some peace recommendations due to the national government has no a roadmap to resolve the conflict between Jakarta and Papua peacefully. The article argues that a continuously informal communication between conflicted parties is a necessary condition, but it is not a sufficient condition to create a positive peace. Therefore, the National Government is strongly suggested to implement an inclusive national dialogue with Papuan people.